From Minor Deeds to Global Consequences: An Scientific & Islamic Reflections on the Butterfly Effect in Ecocide, Genocide, and Its Application in Education - Mike Kurniasih; Aprillyana Dwi Utami (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study try to examines the relationship between the Butterfly Effect theory in complex systems and Islamic ethical values, along with its implications for education. The Butterfly Effect suggests that small changes in a system can trigger large and unpredictable impacts. In Islam, this aligns with the principle that every deed, no matter how small, is accounted for (Qur’an, Az-Zalzalah: 7–8), and that humans have the role of khalifah (steward) to maintain the balance of the earth (Qur’an, Al-Baqarah: 30). Using a qualitative method based on literature review, this study analyzes Islamic and academic literature from the fields of science, religion, education, philosophy, and ecology. The findings show that micro-actions such as consumption choices, speech, or daily lifestyle patterns can serve as tipping points for systemic change either toward collective benefit (maslahah) or destruction. Historical examples such as the actions of Greta Thunberg, Gandhi, Rosa Parks, and the Chipko Movement demonstrate the transformative power of small acts. In the Islamic context, small deeds performed sincerely and consistently possess profound spiritual and social power. Ecocide and genocide are also understood as cumulative results of often overlooked micro-destructive behaviors. Therefore, education must be directed toward fostering moral and ecological awareness from an early age. This study recommends an Islamic ecopedagogy approach as a transformative educational model that integrates tawhid (the oneness of God), holistic systems thinking, and ecological responsibility. A curriculum based on small deeds aims to cultivate a generation that is conscious, responsible, and actively engaged in sustaining the earth and promoting social justice.